Structural vibration : a uniform accurate solution of laminated beams, plates and shells with general boundary conditions /: a uniform accurate solution of laminated beams, plates and shells with general boundary conditions. ([2015]) - Jin, Guoyong; Ye, Tiangui; Su, Zhu
No abstract available